Remaking the prisons of the market democracies: new experts, old guards and politics in the carceral fields of Argentina and Chile - Hathazy, Paul Carlos (2016)
This article explains the evolution of prison policies in Argentina and Chile after the dual transition to neoliberalism and democracy addressing in particular the renewal of correctionalist prison rationalities propelled by human rights and managerialism expertise, their specific articulations and the differential institutionalization in the state. Going beyond objectivist descriptions of prison expansion, I delve into the emergence of a new symbolic order in democratic times that prompted the unexpected revival of rehabilitation programs and increased formalization of prisons regimes and account for their progressive subordination to security priorities. To explain these particular evolutions that contradict predictions of a direct drift toward a purely warehousing prison with greater informality under neoliberalism in Latin America, I engage in a comparative field analysis, analyzing the structure and dynamics within what I call carceral fields to account for the introduction of new rationalities and for their differential institutionalization in prison bureaucracies. After presenting the concept of carceral field and reviewing alternative accounts of prison change in Latin America, I show that the emergence of these rationalities follow the entrance of new experts within the field in democratic times, and account for their differential incorporation in prison policies and regimes analyzing how the interests of prison officers and political agents and increasing overcrowding conditioned the experts’ strategies. This study, based on documentary evidence and interview data, demonstrates that these new legal and economic rationalities do not oppose drifts toward populist punitivism, but give it a progressive face, legitimating punitive policies while providing new power resources to elite prison administrators.